SAT0226 Circulating Serum Levels of Cortisol Are Associated with The Pain Threshold in Systemic Sclerosis: Correlations with Depression. (15th July 2016) - Bagnato, G.; Cordova, F.; Sciortino, D.; Fiorenza, A.; Ferrera, A.; Coppolino, G.; Sangari, D.; Roberts, W.N.; Gangemi, S.; Bruno, A.; Muscatello, M.R.A.; Pandolfo, G.; et al.
Abstract : Background: Previous studies on pain prevalence among systemic sclerosis (SSc) patients confirms its prominent role in disease outcomes 1 . Although pain perception is receiving more importance among patient-reported outcomes in SSc research, still its interface with mood disorders and immune system need to be further elucidated. The prevalence of clinically significant symptoms of depression or anxiety in SSc varies between 36% and 65% according to the evaluation used, and are rather associated with increased disability and altered HRQoL, than with disease-specific organ manifestations. An endocrine influence on pain perception and threshold is supported by robust evidences, more specifically related to sex, adrenal and thyroid hormones. Objectives: To analyze the association between pain threshold, depression and cortisol serum levels in systemic sclerosis patients, major depression disorder patients and healthy controls. Methods: Thirty SSc patients, 30 major depressive disorder (MDD) patients and 30 healthy controls completed the study. All participants underwent pressure pain threshold (PPT) assessment through an algometer in three anatomical surfaces, the ungula bed (UPPT) and the metacarpophalangeal joint (MPPT) of the second finger of the right hand and the anterior portion of the quadriceps muscle (QPPT), and depression evaluation, assessed by patient health questionnaire 9 (PHQ-9). Serum cortisol was measured in SSc and MDD patients for further analysis. Patients under treatment with corticosteroids were excluded. Results: PHQ-9 values showed that 15% of SSc patients had no signs of depression, while 30% had mild and another 30% moderate signs of depression, 18% moderate/severe and 9% severe signs. Among MDD patients, PHQ-9 12% had mild depression, 45% moderate, 15 moderate to severe and 28% severe depression. PHQ-9 scores were significantly higher in SSc and MDD compared to controls (p<0.0001) and furthermore MDD patients had significantly higher than those reported by SSc patients (p<0.005). Pain threshold scores were significantly lower in SSc and MDD patients compared to healthy subjects in all sites (p<0.0001). In addition, SSc patients showed significant lower pain thresholds when compared to MDD, regardless the site of measurement (UPPT: p=0.0053; MPPT: p=0.0121; QPPT: p=0.0086). In addition, cortisol serum levels were significantly higher in MDD patients compared to SSc (17.1±5.7 vs 8.5±3.7 μg/dl; p<0.0001). Both in SSc and MDD a significant direct correlation was observed between cortisol serum levels and PPT in all sites. Conclusions: The interface between pain, depression and cortisol could represent an additional complex aspect of care of patients with either SSc or MDD. References: Schieir O, Thombs BD, Hudson M, Boivin JF, Steele R, Bernatsky S, Hanley J, Baron M; Canadian Scleroderma Research Group. Prevalence, severity, and clinical correlates of pain in patients with systemic sclerosis. Arthritis Care Res (Hoboken). 2010 Mar;62(3):409–17. Disclosure of Interest: None declared